Diagnosing hemp and cannabis crop diseases - Wang, Shouhua, (Plant pathologist) (CABI, CAB International, 2021)
"Extensively illustrated with over 300 colour photographs, this book describes how to diagnose hemp and cannabis crop diseases. It is aimed as a practical guide for farmers and growers, as well as researchers in plant pathology"--